1997
DOI: 10.3168/jds.s0022-0302(97)76290-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatment on the Antigen-Binding Activity of Anti-Peroxidase Immunoglobulins in Bovine Colostrum

Abstract: After intramammary immunization with horseradish peroxidase, bovine colostrum containing anti-peroxidase immunoglobulins (Ig) was obtained. Thermoresistance of the antigen-binding region of these Ig was studied using a direct competitive ELISA. This technique is based on the competition between the anti-peroxidase IgG coated to the plate and the anti-peroxidase IgG contained in the colostrum to bind peroxidase, the antigen, and the enzyme responsible for development of the color of the assay. Thus, the degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 18 publications
5
41
2
1
Order By: Relevance
“…Other studies of the thermal denaturation of bovine milk IgG have variously reported reaction orders between 1.2 and 2.5, with fractional orders indicating multiple simultaneous unfolding and aggregation pathways (Cao et al, 2007;Dominguez et al, 1997;Law, 1995;Levieux, Levieux, El-Hatmi, & Rigaudiere, 2006;Mainer et al, 1997). It is difficult to rationalise the discrepancies in reported denaturation reaction order under comparable conditions, although the dependency of the rate constant on initial concentration and on temperature, where unfolding and aggregation may be rate-determining over different ranges, will be contributing factors.…”
Section: Denaturation Studiesmentioning
confidence: 84%
See 2 more Smart Citations
“…Other studies of the thermal denaturation of bovine milk IgG have variously reported reaction orders between 1.2 and 2.5, with fractional orders indicating multiple simultaneous unfolding and aggregation pathways (Cao et al, 2007;Dominguez et al, 1997;Law, 1995;Levieux, Levieux, El-Hatmi, & Rigaudiere, 2006;Mainer et al, 1997). It is difficult to rationalise the discrepancies in reported denaturation reaction order under comparable conditions, although the dependency of the rate constant on initial concentration and on temperature, where unfolding and aggregation may be rate-determining over different ranges, will be contributing factors.…”
Section: Denaturation Studiesmentioning
confidence: 84%
“…However, few studies have considered differentiation of Fab and Fc domains within bovine lacteal IgG with respect to relative conformational stability, and the potential for other milk components to moderate this stability, and conclusions remain equivocal (Cao et al, 2007;Dominguez et al, 1997Dominguez et al, , 2001Li et al, 2005;Ohnuki & Otani, 2005). A study of the stability of mouse monoclonal IgG by calorimetric and circular dichroism techniques has revealed independent denaturation transitions of Fab and Fc domains, with each region being influenced distinctively by thermal or pH stress (Vermeer & Norde, 2000).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…For n ≠ 1, the general rate equation can be solved to get: [207], 1.5 [208,209], 2.0 [210,211] or 2.5 [212]. The order of the reaction is typically determined by fitting the experimental data using different reaction orders, and assigning the order with highest R 2 value.…”
Section: Comparison Of Es-dma With Secmentioning
confidence: 99%
“…Algunos de los patógenos que pueden estar presentes en el calostro, ya sea provenientes de la glándula mamaria o de la contaminación en el manejo del mismo y que pueden ser transmitidos a las terneras incluyen: Mycobacterium avium spp. Paratuberculosis, Salmonella spp., Micoplasma spp., Listeria monocytogens Campylobacter spp., Mycobacterium bovis y Escherichia coli (Dominguez 1997;Stabel 2001;Stabel 2004;Stewart 2005;Godden et al 2006). Estos agentes infecciosos pueden ocasionar enfermedades como la enteritis y septicemia.…”
Section: Pasteurización Del Calostrounclassified